Loading...

49 plus 10 equals 59.

36+8=44 49+42=91 Therefore,if both equations are not equivalent, then 36+8 doesn't equal 49+42

5x+49 = 8x+13 49-13 = 8x-5x 36 = 3x x = 12

1 + 4 + 16 + 25 + 36 + 49 = 131

49 plus 7 equals 56.

4849494949505050------394

20 plus 49 equals 69

-x2+14x=49

49 * 36

49

49 + 72 + 68 = 189

49+18= 67

18 + 31 = 49

It is: 14+35 = 49

36x49= 1,764

49 multiplied by 36 is 1,764.

48 + 1 = 49

455

49

49

102

49

49 932

It simplifies to 7k = 49 which gives k = 7.

3 + 8 - (10 x 6) = 11 - 60 = -49